(untitled) (Discourse of Law and Administration, 2022)
In recent years, the problem of fly tipping has increased. This one phenomenon corresponds to the numerous legal regulations. The diversity of procedures often cause disputes between different authorities. The subject of the paper is therefore to analyze whether the legal order in this field creates chaos or a complementary system. Furthermore, the subject of the paper is the question whether there are any conflict-of-law regimes allowing for effective prevention of illegal landfills.